PENGARUH TIPE EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR PKn KELAS IV SDN 05 MHU - Arvina, Arvina; Sabri, Tahmid; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aims to determine mastery of the effect of cooperative type example non example toward learning outcomes civic education fourth grades SDN 05 MHU. The form of research used is quasy exsperimental design with research design time series design. The sample populations that used is saturated sample because the entire populations is the sampled. The sample in this research is all fourth graders, consisting of ten female students and seven male students. The data collection tools used are observation sheet and 25 multiple choice question. Based on statistical calculation from the everage pre test result of 45,85 and post test average of 66,55. From the calculation of the effect size obtained ES=1,843 with a high categories, it means giving a high influence on the learning outcomes of the fourth graders SDN 05 MHU students.Keywords : Type example non example, Learning outcomes, Civic education.